An Analysis of Parents’ Attitude towards TEFL in Islamic Elementary School of Wahdah Islamiyah - Mursad Syam Tonra; Kisman Salija; Haryanto Atmowardoyo (Har Press Indonesia, 2021)
This study is qualitative research that aimed to understand the parents’ opinion and attitude toward TEFL at Elementary School of Wahdah Islamiyah. The study focused on the issue of the clash between Islamic values and Western values in learning English. The 5 participants were chosen based on the educational background: Master’s Degree, Bachelor‘s Degree, Senior High School, Junior High School and Elementary School. The research data were obtained by the interviewing from 5 participants. The protocol consists of 10 questions. The results are: 1). The opinion of parents who were interviewed as participants indicates positive opinions and supported the implementation of English learning in Islamic school, 2). The participants considered English lesson as important lesson for their children, 3). The attitudes shown by the participants towards English lesson in Islamic schools are a positive attitude, a supportive attitude and a constructive attitude in the development and process of English learning in Islamic schools, 4). The parents’ positive attitude indicated on how they try to help their children in learning English and also refused the idea of removing English lesson from Islamic elementary school, 5). The participants, consist of parents of students from Wahdah Islamiyah Elementary school, have flexible mindset and open-minded, 6). Great synergy among parents and teachers in educational environment at school would enhance the quality of English learning.